THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT AND CUSTOMER VALUE ON CUSTOMER SATISFACTION OF SERVICES AND ITS IMPACT ON CUSTOMER LOYALTYIN PT. BPR RANGKIANG AUR - Yullya Ramadonna; Nasf Nasf; Zakaria Aziz (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2019)
This research aims to reveal, know and analyze the effect of customer relationship management and customer value on customer satisfaction of services and its impact on customer loyalty in PT. BPR Rangkiang Aur. The technique of sampling Propotional Cluster Random Sampling. The sample of this study is 280 people. The results of the research are: 1) Customer Relationship management has a significant and positive impact on customer satisfaction of BPR Rangkiang Aur customers. 2) Costumer Value has a significant and positive effect on customer satisfaction of BPR Rangkiang Aur customers. 3) Satisfaction has a significant and positive impact on customer loyalty of BPR Rangkiang Aur customers. 4) Customer satisfaction to mediate on Influence of Customer Relationship Management to Loyalty of BPR Rangkiang Aur Customer. 5) Customer satisfaction to mediate on the influence of Customer Value on Customer Loyalty BPR Rangkiang Aur.Keywords: Customer Relationship Management, Costumer Value, Customer Satisfaction andCustomer Loyalty.